2018
DOI: 10.21475/poj.11.01.18.pne1020
|View full text |Cite
|
Sign up to set email alerts
|

CrMYC1 transcription factor overexpression promotes the production of low abundance terpenoid indole alkaloids in Catharanthus roseus

Abstract: Catharanthus roseus is known as the only source for the low-abundance anticancer agents namely vinblastine and vincristine. Fine tuning of accumulation of such secondary metabolites is highly governed by the regulatory genes. Among these genes, Catharanthus roseus MYC1 (CrMYC1) is known as one of the key transcription factors regulating the biosynthesis of terpenoid indole alkaloid metabolites in C. roseus. In this study, CrMYC1 coding sequence (AF283506) was isolated and cloned in PBI121 plant binary vector. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Transient expression was used to overexpress the CrMYC1 gene in C. roseus leaves and it was reported a 3 fold increase in catharanthine and vinblastine content, 2 days after agroinfiltration. Although CrMYC1 gene needs to be further characterized, it was concluded that it was a suitable candidate for alkaloid enrichment in C. roseus via metabolic engineering ( Sazegari et al, 2018 ). It is advisable to check the levels of transcripts and metabolites at different time points to find an optimal time, as well as replicate experiments on a large number of plants with different growth stages, since transient expression could be affected by the developmental and physiological state of the plants ( Sazegari et al, 2018 ).…”
Section: Plant Transformation Methods To Enhance Alkaloids Contentmentioning
confidence: 99%
“…Transient expression was used to overexpress the CrMYC1 gene in C. roseus leaves and it was reported a 3 fold increase in catharanthine and vinblastine content, 2 days after agroinfiltration. Although CrMYC1 gene needs to be further characterized, it was concluded that it was a suitable candidate for alkaloid enrichment in C. roseus via metabolic engineering ( Sazegari et al, 2018 ). It is advisable to check the levels of transcripts and metabolites at different time points to find an optimal time, as well as replicate experiments on a large number of plants with different growth stages, since transient expression could be affected by the developmental and physiological state of the plants ( Sazegari et al, 2018 ).…”
Section: Plant Transformation Methods To Enhance Alkaloids Contentmentioning
confidence: 99%
“…Similar to other valuable plant metabolites, vinblastine is also of interest to modern plant biotechnology and many studies have attempted to increase its production in plant tissues. One study examined the effect of overexpression of the MYC1 transcription factor (CrMYC1) in C. roseus [90]. CrMYC1 has been characterized as one of the main components regulating the biosynthesis of terpenoid indole alkaloid metabolites in this plant.…”
Section: Vinblastinementioning
confidence: 99%
“…The BIS1 transcriptional activator turns on expression of all genes analyzed that encode proteins in the metabolic pathway between geranyl diphosphate and loganic acid (Van Moerkercke et al, 2015;Van Moerkercke et al, 2016;Schweizer et al, 2018). The CrMYC1 transcriptional activator was identified based on its ability to bind the STR promoter (Chatel et al, 2003) and overexpression of CrMYC1 increases vinblastine, vincristine and catharanthine levels (Sazegari et al, 2018). However, Full-size  DOI: 10.7717/peerj.11624/fig- 1 information regarding which TIA and TIA-related genes may be regulated by CrMYC1 is currently lacking.…”
Section: Introductionmentioning
confidence: 99%